Perceived Stress and Coping Strategies Utilized by Nursing Students of Bachelor Level in the COVID-19 Pandemic - Singh, Ajanta Maharjan; Kalikotay, Bhagawaty (Medical Journal of Eastern Nepal, 2024)
Background: The COVID-19 global pandemic was challenging for the general population and the students as well. The classes moved to online and stayed at home with a safe execution was ordered. Many students faced distressing changes. Both behavioral and psychological coping strategies were employed to minimize stress. This study aimed to assess the perceived stress and coping strategies used during the COVID-19 pandemic by nursing students.Methods: A cross-sectional descriptive design was used. Nursing students studying bachelor level in the Constituent Colleges of Tribhuvan University were the study population. A structured self-administered online questionnaire containing demographic information, a perceived stress scale, and a modified brief cope scale was used. The obtained data were analyzed using SPSS version 16 using descriptive and inferential statistics.Results: The mean age of the respondents was 25.76+3.13 years, almost half (42.9%) were from Maharajgunj Nursing Campus. More than half (53.8%) were studying in a Bachelor of Nursing Science (BNS) in their third year, among them 9.2% had medical problems. Only a few (5.4%) suffered from COVID-19 during this study period. Around 14.7% perceived a high level, 61.4% moderate level and 23.9% perceived a low stress level. The mean scores of approach coping strategies and an avoidant coping strategies were found to be 35.2 and 23.1 respectively. No association existed between the respondents' stress levels and the selected demographic variables.Conclusion: Most of the respondents perceived a moderate level of stress and used a healthy coping strategies to minimize stress during the COVID-19 pandemic.